HuR ablation destabilizes Foxp3 mRNA and impairs regulatory T cell function, contributing to an autoimmune phenotype - Fattahi, Fatemeh; Ellis, Jason S.; Vallance, Laura; Bahleda, Kristin; Holden, Julia; Socha, Sarah; Meier, Joshua; Gomez-Rivera, Francisco; Atasoy, Ulus (Frontiers in Immunology, 2025)
IntroductionThe RNA-binding protein HuR (Elavl1), a key post-transcriptional regulator, plays a critical role in T cell activation and function by stabilizing target mRNAs. To investigate the role of HuR in regulatory T cell (Treg) function, we generated the Foxp3YFP/Cre HuRfl/fl mouse model.MethodsIn this model, homozygous females and hemizygous males for Foxp3 developed a scurfy-like phenotype displaying autoimmune features, including failure to thrive, splenomegaly, hair loss, tail stippling, and widespread multi-organ immune cell infiltration. Molecular analysis included direct interaction studies between HuR and Foxp3 mRNA to assess mRNA stability, RNA sequencing of YFP⁺ Tregs, Protein-Protein Interaction (PPI) analysis, qPCR, and Treg functional assays.ResultsTo our knowledge, this is the first study demonstrating that HuR directly binds and stabilizes Foxp3 mRNA in Tregs, using a novel Treg-specific HuR-deficient mouse model, with implications for autoimmune regulation. Foxp3 mRNA stability and expression were significantly reduced in Tregs from these HuR KO mice, despite higher frequencies of YFP⁺ Tregs. RNA sequencing revealed significant dysregulation of several pathways, including the T helper differentiation pathway, in which Foxp3 played a central role. PPI analysis showed a direct link between Foxp3 and Rorc (encoding RORγt), connecting Foxp3 to the T cell differentiation pathway via IL-23R. Our qPCR analysis supported these findings. Functional assays demonstrated a reduction in the suppressive capacity of HuR-deficient Tregs.ConclusionThese findings together suggest that ablation of HuR in Tregs disrupts Foxp3 expression and Treg function, likely through dysregulation of T cell differentiation pathways involving RORγt. This potentially contributes to a disrupted Treg–Th17 axis and autoimmune dysfunction. These data suggest that HuR-mediated post-transcriptional regulation contributes to maintaining Foxp3 expression and immune homeostasis, although compensatory mechanisms such as increased IL-10 expression may also be involved.